Global research of future trends and development in cash holding: a bibliometric review - Shafiq, Ume Salma; Selamat, Aslam Izah; Mohd Nor, Normaziah; Amin Noordin, Bany Ariffin (Human Resource Management Academic Research Society, 2022)
Cash holdings are becoming a growing issue for worldwide scholars in finance to understand the importance of the strategic approach of corporate cash policy of cash reserves. In practice, firms have faced challenges in adopting an appropriate corporate cash holdings policy. It would be appropriate to study the notions of cash holding (CH) to explore suitable strategies to overcome the inadequacy of financial policy of cash reserves in the financial system worldwide. Thus, this paper aims to conduct a bibliometric analysis and fill this literature gap by identifying and evaluating the current status and developing trends of the cash holdings domain to provide meaningful insights and assist in further discussion. Bibliometric studies have proven to be beneficial in helping researchers better exploring the current research trends in a particular field of research. From Scopus database, this study identifies the knowledge evolution trend in the field of cash reserves or cash holdings, where 1,073 published articles from year 1971 to 2022 were reported. The current study's findings demonstrate that the number of publications in the domain of cash holdings has intensified in the past few years. The results also identify that Economics, Econometrics, and Finance were the more popular subject categories in the field of cash holdings from the past few decades. In terms of keyword analysis, the most frequently used keyword by authors associated with cash holdings are corporate governance and financial constraints. Moreover, co-authorship with researchers finds that most collaboration has taken place among United States, China, and the United Kingdom. Finally, citation analysis reveals the Journal of Corporate Finance dominates this field of research. Future strings of research should focus on the cash holdings and financial constraints, investment and external drivers that have an effect on cash holdings.